The relationship between academic procrastination with parenting styles and self-esteem among primary school students - Lim, Siao Kee (2021)
Academic procrastination is a deliberate postponement of school-related activities. The purpose of this study is to investigate the relationship between academic procrastination with parenting styles and self-esteem among primary school students. Through the cluster sampling technique, a sample of 103 Year 5 primary school students were selected: 53 of which are boys and 50 of which are girls. In this current study, the survey data was collected using modified Procrastination Assessment Scale - Students (PASS) developed by Solomon and Rothblum (1984), Parental Authority Questionnaire - Short Version (PAQ - Short Version) by Alkharusi, Aldhafri, Kazem, Alzubiadi, and Al-Bahrani (2011) and Rosenberg Self-esteem Scale (RSE) originated by Rosenberg (1965). The findings revealed that there were significant relationships between three different parenting styles and academic procrastination. No significant relationship between self-esteem and academic procrastination was found in this study. The results also indicated that authoritative parenting style was significantly related to self-esteem, in contrast, authoritarian and permissive parenting styles were no significant related to selfesteem. Several implications of the current study were discussed as well as the recommendations for further research.